Sikh historical memory as an ideological justification for Khalistan. (2nd January 2018) - Kataria, Shyamal
ABSTRACT: The Khalistan movement was an armed secessionist struggle carried out by the Sikhs of Punjab, northern India, which spanned the period between 1981 and 1993. In parallel with other such insurgencies around the world, it is evident that the Khalistan movement had a strong ideological underpinning which not only helped to fuel its rise, but also helped to sustain it throughout its tenure. In this regard, the reference point for ideological justification was very much the past experiences and episodes of the Sikh community, or, to be precise, their 'historical memory' of these. This article focuses its attention on identifying, describing and interrogating the strength of the ideological justifications that were extracted from Sikh historical memory in support of Khalistan.